Menentukan Varietas Bibit Unggul Bawang merah Menggunakan metode SAW - Arman Naufal; Ahmad Selao; Mughaffir Yunus (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
The large number of types of shallot seeds makes it difficult for farmers to choose quality seeds that are in accordance with land conditions, which causes crop yields to be less than optimal. The purpose of the research is to create an application that can help farmers select optimally superior seeds according to agricultural land conditions. The research uses a type of quantitative research based on data obtained at the Anggeraja Agricultural Extension Agency, which will be carried out for three months in 2024 using web technology and the SAW method. The research produced a WEB based application that can determine superior seeds and evaluate the quality of seedlings based on factors such as land height, harvest age, soil pH, tuber size, moisture content, disease resistance, and variety purity. The results of the test show that this application is able to identify the seeds that have the best characteristics.